Towards a workable renewable energy framework inSouth Africa - Jooste, D (Department of Public Law, 2014)
This dissertation aims to determine whether a workable legal framework forrenewable energy (RE) exists in South Africa by comparing the country'sexisting policy and legislative frameworks in order to highlight strengths andweaknesses, and juxtaposing this overall position against contemporaryforeign legislation from the United States in an effort to discern relevant andviable best practices. Key issues that are considered include: theGovernment's commitment to RE and energy efficiency; environmentalprotection and RE as drivers for social development; job creation andsustainable economic growth; the governance of and relevant institutions inthe energy sector; public participation, education and access to information interms of RE; and, finally, the use of market-based instruments for the supportof RE in South Africa.The research found that South Africa's legal framework is largely on par withinternational best practice in terms of the above issues. Rather than a lack ofsubstantive content in the legal framework, implementation and politicalcommitment (buy-in) appears to be inadequate. However, issues on whichSouth Africa's legal framework is found to be wanting include: a lack ofbinding RE targets and full costing in the energy sector; the Government'sreluctance to enter public–private partnerships despite its current lack ofcapacity; and an almost unfettered executive discretion in terms of REdevelopment and deployment.This dissertation concludes that the Government has failed to take a longtermview of the energy sector, choosing, instead, to accomplish interimsocial upliftment through short-term utilization of coal power at the expenseof the environment and future generations. This points to inadequatetransparency and institutional accountability in the sector. Vague legislativemandates and a seeming lack of political will and insight in South Africanecessitates a comprehensive legislative review before RE can play a part inthe future development of the country.